Quality of life, effectiveness, and safety of aflibercept plus FOLFIRI in older patients with metastatic colorectal cancer: an analysis of the prospective QoLiTrap study - Piringer, Gudrun; Thaler, Josef; Anchisi, Sandro; Geffriaud-Ricouard, Christine; Gueldner, Max; Scholten, Felicitas; Derigs, Hans-Günter; Bohanes, Pierre; Grünberger, Birgit; Schwarz, Leonora; von Moos, Roger; Hofheinz, Ralf-Dieter (Journal of geriatric oncology, 2023)
Introduction - Colorectal cancer (CRC) mainly affects older patients. The pivotal VELOUR phase III trial of aflibercept plus FOLFIRI in metastatic CRC (mCRC) included only 5.9% of patients aged ≥75 years. Herein, we report a preplanned analysis from QoLiTrap, a large prospective observational study evaluating the impact of age on quality of life (QoL), effectiveness, and safety of aflibercept plus FOLFIRI in daily clinical practice in Europe. - Materials and Methods - Enrolled patients had progressive mCRC, had failed a prior oxaliplatin-based regimen, and had received aflibercept (4 mg/kg) plus FOLFIRI every two weeks until disease progression, death, unacceptable toxicity, or physician/patient decision. Analyses were performed by age classes (<60, 60-64, 65-69, 70-74, and ≥ 75 years). The primary endpoint was the percentage of patients whose global health status (GHS) of the European Organization for the Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) was maintained (i.e., no worsening from baseline by at least 5% over a 12-week treatment). Secondary endpoints included tumor objective response rate (ORR), progression-free survival (PFS), overall survival (OS), and safety. - Results - Overall, 1277 patients (<60 years, n = 327; 60-64 years, n = 231; 65-69 years, n = 227; 70-74 years, n = 259; and ≥ 75 years, n = 233) were treated, of whom 872 were evaluable for QoL. GHS was maintained in 36.5%, 41.6%, 38.9%, 41.8%, and 44.8% of patients aged <60, 60-64, 65-69, 70-74, and ≥ 75 years, respectively. Age did not influence PFS (median 7.8 months), OS (median 14.4 months), or ORR (20.8%). Number of cycles, dose delays for any cause, and dose reductions for adverse events (AEs) were comparable between age classes. Grade ≥ 3 AEs occurred in 47.7%, 51.9%, 51.5%, 55.2%, and 55.8% of patients aged <60, 60-64, 65-69, 70-74, and ≥ 75 years, respectively. The main grade ≥ 3 AEs were hypertension (11.2%) and diarrhea (9%) in patients aged ≥75 years. - Discussion - The results suggest that aflibercept plus FOLFIRI maintains QoL and retains its activity, including a high objective tumor response, regardless of age and treatment line. In fit older patients, the safety profile seems manageable, with no new safety signals.